SCHOOL BASED TEACHER DEVELOPMENT STUDY ABOUT A SCHOOL AS PROFESSIONAL LEARNING COMMUNITY - Furqon, Ahmad (Universitas Pendidikan Indonesia, 2019)
The teacher's understanding of CPD is still very low. The main objective of this research is to obtain a picture of school-based teacher development through PLC in the continuous professional development in schools.The research method used is qualitative method. Pre-field includes literature review and field survey. Phase of field work, researcher entered the field in order to collect data. In the data analysis phase the researcher conducts a series of qualitative data analysis process up to the interpretation of the data. In addition, the process of data triangulation compared with library theory. While the evaluation and reporting stage conducted consultation and guidance and reporting of research results.The research findings indicate that the elements of PLC forming are commitment, responsibility, usefulness, collaboration collegial, as well as school culture and climate. While the role of the principal in this PLC is as an instructional leader, motivator, and facilitator. The conclusion of the research shows that PLC is able to promote CPD which leads to improving the quality of learning service.